On Expertise : Cultivating Character, Goodwill, and Practical Wisdom - Mehlenbacher, Ashley Rose, 1983- (Book collections on Project MUSE., 2022)
"A rhetorical account of expertise and expert status that is informed by research in allied fields, including Science, Technology, and Society studies, psychology, education, and philosophy"--